Penerapan Sistem Pendukung Keputusan Seleksi Dosen Non Komputer Terbaik Menggunakan Metode Weighted Product (WP) - Lumban, Romayani; Muhammad Syahrizal (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Lecturers are individuals who have professional and scientific expertise, with the main task of changing, developing and disseminating knowledge, technology and art through educational activities, research and community service. Until now, the selection process for Non-Computer Lecturers has focused on experience as an educator, although there are several other criteria that can be used as a basis for selecting Non-Computer Lecturers. These criteria include Grade Point Average (GPA), ability to collaborate in a team, physical and mental health, expertise in interpersonal skills, and ability in Micro Teaching. The selection process for Non-Computer Lecturers requires support from a decision support system (DSS). DSS is part of a computer-based information system (including knowledge-based systems) that is used to assist in decision making in various types of organizations or entities. In this research, the Weighted Product (WP) method is used to select the best Non-Computer Lecturers. The choice of this method is based on its ability to evaluate and select the best solution from a variety of available alternatives. The results obtained from this research are that alternative A1 with the name Lecturer